The Environmental and Climatic CAP Measures in Poland vs. Farmers’ Expectations—Regional Analysis - Ewa Kiryluk-Dryjska; Agnieszka Baer-Nawrocka; Obinna Okereke (Energies, 2022)
The Common Agricultural Policy of the European Union remains at the top tier of the union’s legacies with the aim of bequeathing a sustainable future for all. Series of actions geared towards reforming the environmental and climate goals of the CAP are constantly being taken. The objective of this paper is to verify if the environmental and climatic CAP measures proposed in Poland’s Strategic Development Plan for Agriculture, for the years 2023–2027, reflect farmers’ preferences regarding the structure of the CAP support. To achieve this goal, we model a hypothetical strategic game involving farmers from different regions. The outcomes of the game were derived from the ex-post analysis of EU funds, in the application for environmental and climatic CAP measures, in addition to the results of simulations of the partial equilibrium model for the agricultural sector (CAPRI). It was found out that farmers from regions with disadvantaged agrarian structures would find it more difficult to cope with new eco-schemes due to the fact that good agricultural practices are rather low in such regions. For the long-term development of Polish agriculture, the agrarian structures need to be improved, as this affects the emission of greenhouse gases. The varying preferences of farmers from different Polish regions in implementing eco-schemes can be balanced by increasing redistributive payments.